Efficacy of silicone foam dressings in preventing pressure injuries in the sacral and heel areas of patients: a meta-analysis - Tingkui Fu; Xiuqin Wu; Biao Yu (Frontiers in Medicine)
BackgroundPressure injury prevention is clinically critical for optimizing patient outcomes. This meta-analysis systematically evaluates the efficacy of silicone foam dressings in preventing pressure injuries specifically in the sacral and heel regions.MethodsA comprehensive literature search was conducted across PubMed, Embase, ClinicalTrials.gov, the Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and Weipu Databases, spanning from database inception to May 10, 2025. Eligible studies were randomized controlled trials (RCTs) investigating silicone foam dressings for pressure injury prevention. Meta-analyses were performed using RevMan 5.4 software.ResultsTen RCTs involving 4,817 patients were included, with 2,670 patients in the silicone foam dressing intervention group. Meta-analysis results showed that silicone foam dressings significantly reduced the incidence of stage I pressure injuries in the sacral region [relative risk (RR) = 0.18, 95% confidence interval (CI): 0.09–0.33, p < 0.001] and heel region (RR = 0.30, 95% CI: 0.14–0.66, p = 0.003). Additionally, these dressings decreased the incidence of stage II and more severe pressure injuries in the sacral region (RR = 0.42, 95% CI: 0.31–0.58, p < 0.001) and heel region (RR = 0.52, 95% CI: 0.27–0.99, p = 0.05).ConclusionSilicone foam dressings exhibit significant efficacy in reducing pressure injury incidence in the sacral and heel regions, supporting their clinical recommendation. However, further research is required to explore their cost-effectiveness and long-term outcomes to strengthen evidence for broader implementation.